Field trials of live gdhA derivative pasteurella multicida B:2 vaccine against haemorrhagic septicaemia in buffaloes - Othman, Rafidah (2013)
Haemorrhagic septicaemia (HS) is an infectious disease mainly affecting cattle and buffalo caused by P. multocida B:2. Vaccination is the best method to prevent HS in cattle and buffaloes. The main objective of this work was to study the field immunoprotective efficacy of the newly constructed live gdhA derivative of P. multocida B:2 to the exposed and in-contact susceptible buffaloes. A retrospective analysis of records of outbreaks of HS in cattle and buffaloes was carried out to study the pattern of the disease in Sabah, Malaysia. A total of 45 outbreaks involving 1,774 susceptible animals were reported for the past 16 years between 1994 and 2009. Outbreaks ranged between 1 and 8 per year, involving 4 of 6 regions in Sabah and occurred in all months except April but with higher frequencies in dry months of June, July and September. The most affected region was Beaufort while the least was Kota Kinabalu, while buffaloes were found to be more frequently involved than cattle. Tawau and Sandakan regions could be considered as HS-free zones while Beaufort, Kudat, Keningau and Kota Kinabalu as endemic zones. A study was conducted on the herd immunity in field buffaloes following initial intranasal exposures to the live gdhA derivative P. multocida B:2 that was given twice at two weeks apart to 30% of the three groups buffaloes. Following vaccination, herd antibody levels in both the areas gradually but insignificantly (p>0.05) increased to peak values by the 6th month and then gradually decline until month 10. Following booster dose at 10th month, the antibodies declined to levels similar to those of unvaccinated animal at 12 to 14 months. Nevertheless, when compared with the control unvaccinated herd, the immune status of both vaccinated herds remained significantly (p<0.05) high throughout the 22-month study period, except for the months 12 to 14. It was concluded that field vaccination using gdhA derivative P.multocida B:2 was able to maintain the herd immunity for 10 months before a booster dose can be considered. Efficacy of HS vaccine containing live gdhA derivative P. multocida B:2 was tested in 60 field buffaloes that were divided into three groups; exposed (Group 1), commingled (Group 2) and control unexposed (Group 3). Buffaloes of group 1 were exposed intranasally to 5 mL vaccine containing 106 CFU/mL of the live gdhA derivative P. multocida B:2, twice at two weeks apart. Twelve months after the first vaccination, three buffaloes from each group were challenged subcutaneously with 109 CFU/mL of live wild-type P. multocida B:2. All buffaloes of groups 1 and 2 survived with mild, transient symptoms while all control unvaccinated buffaloes developed severe signs of HS and were killed humanely between 28h and 38h post-challenge with signs and lesions typical of HS. The gdhA derivative vaccine successfully induced systemic immunity and spread the vaccinal strain to the in-contact animals, this vaccine effectively protect both exposed and in-contact buffaloes against challenge with the virulent parent strain. Control unexposed buffaloes succumbed to the infection showed severe microscopic and ultrastructural lesions typical of HS with the average total microscopic lesion scoring was 2.13±0.19, it was significantly (p<0.05) higher than those of vaccinated and commingled buffaloes with average score of 0.06±0.26 and 0.63±0.29, respectively. The effect of stress using dexamethasone on protective efficacy of the live gdhA derivative P. multocida B:2 against challenge by wild-type P. multocida B:2 was studied. Nine buffaloes were selected and divided into 3 groups; exposed (Group 1), commingled (Group 2) and control unexposed (Group 3). Buffaloes of Group 1 were exposed intranasally to 106 CFU/mL of the gdhA derivative P. multocida B:2, twice at two weeks apart. At the end of 12- month period, all buffaloes were injected intramuscularly with dexamethasone at the dose rate of 1 mg/kg body weight for 3 consecutive days. At the end of the 3-day dexamethasone treatment, all buffaloes were challenged subcutaneously with 109 CFU/mL of wild-type P. multocida B:2. There was significant (P<0.05) increase in the IgG levels in Groups 1 and 2 following the intranasal exposure. The dexamethasone treatment resulted in significant (P<0.05) and rapid reduction in the IgG levels in the control Group 3 but Groups 1 and 2 showed insignificant (P>0.05) reduction. Following challenge, all control Group 3 succumbed to the infection while buffaloes of Groups 1 and 2 survived the challenge. Dexamethasone injections did not significantly reduce the protective efficacy of the live attenuated gdhA derivative P. multocida B:2 but significantly predisposed unvaccinated buffaloes to the infection. As a conclusion, vaccination plays a major role and is the only practical approach to control HS. Vaccination should be concentrated within the endemic areas or ‘hot spots’ where HS outbreaks have been reported within the last 3 years. The vaccination must cover at least 70% of the cattle and buffalo populations. This study revealed that intranasal live attenuated gdhA derivative P. multocida B:2 vaccine was able to provide protection between 8 and 10 months. The annual use of intranasal live attenuated gdhA derivative P. multocida B:2 that permit self-vaccination among free-roaming buffalo within endemic or hot spot areas is recommended to increase the vaccination coverage. This, of course, needs to be followed by sero-surveillance.